Family and social networks after bereavement: experiences of support, change and isolation - Breen, L.; O'Connor, Moira (Wiley-Blackwell, 2010)
The role of family and social support networks on grief experiences following the death of a family member in a road traffic accident is explored. Twenty-one bereaved informants were interviewed and the data analysed using grounded theory methodology. We outline the ways in which a crash fatality impacts upon familial and social relationships. The data clearly demonstrate that although the death of a loved one precipitated closer familial and social bonds in some instances, it was more common that those relationships deteriorated and collapsed. Implications for service delivery, grief education and research are discussed.